Evaluation of a Smartphone Application on the Reduction of Attentional Bias Toward Alcohol Among Students† - Flaudias, Valentin; Zerhouni, Oulmann; Chakroun-Baggioni, Nadia; De Chazeron, Ingrid; Llorca, Pierre-Michel; Brousse, Georges (Frontiers in Psychology, 2022)
Context The recent development of “serious games” has produced encouraging results in maintaining adherence to health-related interventions. In alcohol research, several studies have shown that computerized training on attentional bias decreases alcohol consumption bias among students. However, these highly controlled experimental situations, do not allow for direct large-scale dissemination. Our objective is to evaluate an attentional bias remediation program using a gamified smartphone training procedure. Methods Fifty students from Clermont-Ferrand University were invited to participate in the study. After a cognitive assessment in the laboratory, the smartphone application was installed on each Student’s smartphone. Participants were randomly assigned to either the alcohol attentional training group or the control group Each student had to complete the 2-min program at least once a day for 15 days. After 15 days, a new cognitive assessment of attention bias was conducted in the laboratory. Forty-seven students were included in the study. Results Our analyses did not show any effect of the cognitive remediation program on attentional bias reduction between the two group [F(1, 44) < 1, p = 0.87], attentional performance [F(1, 45) = 1.63, p = 0.20] or inhibitory abilities [F(1, 45) < 1, p = 0.73]. These results were confirmed by Bayesian analyses. Discussion Despite the absence of group effects, both the alcohol and control (non-alcohol) version of this program appeared to reduce attentional bias and increase inhibition capacities in the subset of participants who had attentional bias for alcohol at baseline This pilot study identifies areas for improvement in smartphone applications for future developments. Attentional bias remediation programs remain an interesting way to explore.